# Integration of Trigonometric Functions

**Differentiation**, in mathematics, the process of finding the derivative, or rate of change, of a function. In contrast, to the abstract nature of the theory behind it, the practical technique of differentiation can be carried out by purely algebraic manipulations, using three basic derivatives, four rules of operation, and a knowledge of how to manipulate functions.

e.g.:Consider a function, x = y^{2}.This function can be differentiated as:

d(y

^{2}) / dy = 2y

However, an **indefinite integral** is a function that takes the anti-derivative of another function. It is represented as an integral symbol (∫), a function, and a derivative of the function at the end. The indefinite integral is an easier way to symbolize an anti-derivative.

Let’s learn what is integration mathematically, the integration of a function f(x) is given by F(x) and it is represented by:

∫f(x)dx = F(x) + CHere R.H.S. of the equation means integral of f(x) with respect to x, F(x) is called anti-derivative or primitive, f(x) is called the integrand, dx is called the integrating agent, C is called constant of integration or arbitrary constant and x is the variable of integration.

### List of some important Indefinite Integrals of Trigonometric Functions

Following is the list of some important formulae of indefinite integrals on basic trigonometric functions to be remembered are as follows:

- ∫ sin x dx = -cos x + C
- ∫ cos x dx = sin x + C
- ∫ sec
^{2}x dx = tan x + C - ∫ cosec
^{2}x dx = -cot x + C - ∫ sec x tan x dx = sec x + C
- ∫ cosec x cot x dx = -cosec x + C
- ∫ tan x dx = ln | sec x | + C
- ∫ cot x dx = ln | sin x | + C
- ∫ sec x dx = ln | sec x + tan x | + C
- ∫ cosec x dx = ln | cosec x – cot x | + C

where dx is the derivative of x, C** **is the constant of integration and ln represents the logarithm of the function inside modulus (| |).

Generally, the problems of indefinite integrals based on trigonometric functions are solved by substitution method. So let’s discuss more about the integration by substitution method as follows:

**Integration by Substitution**

In this method of integration by substitution, any given integral is transformed into a simple form of integral by substituting the independent variable by others.

Consider an integral, ∫ 3x

^{2}sin (x^{3}) dx.In order to evaluate the given integral lets substitute any variable by a new variable as:

Let x

^{3}be t for the given integral.Then,

dt = 3x

^{2}dxTherefore,

∫ 3x

^{2}sin (x^{3}) dx = ∫ sin (x^{3}) (3x^{2}dx)Now, substitute t for x

^{3}and dt for 3x^{2}dx in the above integral.∫ 3x

^{2}sin (x^{3}) dx = ∫ sin (t) (dt)= -cos t + C (Since, ∫ sin x dx = -cos x + C)

Again, substitute back x

^{3}for t in the expression as:

∫ 3x^{2}sin (x^{3}) dx = -cos x^{3}+ C

Hence, the General Form of integration by substitution is:

**∫ f(g(x)).g'(x).dx = f(t).dx **(where t = g(x))

Usually the method of integration by substitution is extremely useful when we make a substitution for a function whose derivative is also present in the integrand. Doing so, the function simplifies and then the basic formulas of integration can be used to integrate the function.

In calculus, the integration by substitution method is also known as the “Reverse Chain Rule” or “U-Substitution Method”. We can use this method to find an integral value when it is set up in the special form. It means that the given integral is of the form:

Now, lets solve some basic problems based on the concepts discussed above as follows:

### Sample Problems

**Problem 1: Determine the integral of the following function: f(x) = cos ^{3} x.**

**Solution:**

Let us consider the integral of the given function as,

I = ∫ cos

^{3}x dxIt can be rewritten as:

I = ∫ (cos x) (cos

^{2}x) dxUse trigonometry identity: cos

^{2}x = 1 – sin^{2}x as,I = ∫ (cos x) (1 – sin

^{2}x) dx= ∫ cos x – cos x sin

^{2}x dx= ∫ cosx dx – ∫ cosx sin

^{2}x dx= sin x – ∫ sin

^{2}x cos x dx. (Since, ∫ cos x dx = sin x + C) ……(1)Let, sin x = t then, cos x dx = dt.

Substitute t for sin x and dt for cos x dx in second term of the above integral.

I = sin x – ∫ t

^{2}dt= sin x – t

^{3}/3 + CAgain, substitute back sin x for t in the expression.

Hence, ∫ cos^{3}x dx = sin x – sin^{3}x / 3 + C.

**Problem 2: If f(x) = sin ^{2} (x) cos^{3} (x) then determine ∫ sin^{2}(x) cos^{3}(x) dx.**

**Solution:**

Let us consider the integral of the given function as,

I = ∫ sin

^{2}(x) cos^{3}(x) dxUse trigonometry identity: cos

^{2 }x = 1 – sin^{2 }x as,I = ∫ sin

^{2 }x (1 – sin^{2 }x) cos x dxLet sin x = t then,

dt = cos x dx

Substitute these in the above integral as,

I = ∫ t

^{2 }(1 – t^{2}) dt= ∫ t

^{2}– t^{4}dt= t

^{3 }/ 3 – t^{5}/ 5 + CSubstitute back the value of t in the above integral as,

Hence, I = sin^{3}x / 3 – sin^{5}x / 5 + C.

**Problem 3: Let f(x) = sin ^{4}(x) then find ∫ f(x)dx. i.e. ∫ sin^{4}(x) dx.**

**Solution:**

Let us consider the integral of the given function as,

I = ∫ sin

^{4}(x) dxor

I = ∫ (sin

^{2}(x))^{2}dxUse trigonometry identity: sin

^{2}(x) = (1 – cos (2x)) / 2 as,I = ∫ {(1 – cos (2x)) / 2}

^{2}dx= (1/4) × ∫ (1+cos

^{2}(2x)- 2 cos2x) dx= (1/4) × ∫ 1 dx + ∫ cos

^{2}(2x) dx – 2 ∫ cos2x dx= (1/4) × [ x + ∫ (1 + cos 4x) / 2 dx – 2 ∫ cos2x dx ]

= (1/4) × [ 3x / 2 + sin 4x / 8 – sin 2x ] + C

= 3x / 8 + sin 4x / 32 – sin 2x / 4 + C

Hence, ∫ sin^{4}(x) dx = 3x / 8 + sin 4x / 32 – sin 2x / 4 + C

**Problem 4: Find the integration of:**

**Solution:**

Let us consider the integral of the given function as,

Let t = tan

^{-1}x ……(1)Now, differentiate both side with respect to x:

dt = 1 / (1+x

^{2}) dxTherefore, the given integral becomes:

I = ∫ e

^{t}dt= e

^{t}+ C …….(2)Substitute the value of (1) in (2) as:

which is the required integration for the given function.

**Problem 5: Find the integral of the function f (x) defined as,**

**f (x) = 2x cos (x ^{2} – 5) dx**

**Solution:**

Let us consider the integral of the given function as,

I = ∫ 2x cos (x

^{2}– 5) dxLet (x

^{2}– 5) = t ……(1)Now differentiate both side with respect to x as,

2x dx = dt

Substituting these values in the above integral,

I = ∫ cos (t) dt

= sin t + C ……(2)

Substitute the value equation (1) in equation (2) as,

I = sin (x

^{2}– 5) + CThis is the required integration for the given function.

**Problem 6: Determine the value of the given indefinite integral, I = ∫ cot (3x +5) dx.**

**Solution:**

The given integral can be written as,

I = ∫ cot (3x +5) dx

= ∫ cos (3x +5) / sin (3x +5) dx

Let, t = sin(3x + 5) so,

dt = 3 cos (3x+5) dx

Therefore,

cos (3x+5) dx = dt / 3

And

I = ∫ dt / 3 sin t

= (1 / 3) ln | t | + C

Replace t by sin (3x+5) in the above expression.

I = (1 / 3) ln | sin (3x+5) | + C

This is the required integration for the given function.

Attention reader! All those who say programming isn’t for kids, just haven’t met the right mentors yet. Join the ** Demo Class for First Step to Coding Course, **specifically **designed for students of class 8 to 12. **

The students will get to learn more about the world of programming in these **free classes** which will definitely help them in making a wise career choice in the future.